Peran Strategis Bakteria pada Bioremediasi Limbah Industri Farmasi di Perairan: Peran Strategis Bakteria pada Bioremediasi Limbah Industri Farmasi di Perairan - Putri Dinatul M; Naura Tahta R; Danish Aulia S.N; Nawal Karina B; Intan Shofiyyatul L; Isnaeni, Isnaeni (Berkala Ilmiah Kimia Farmasi, 2025)
Bioremediation is an environmental restoration technique that uses microorganisms to decompose hazardous waste, including pharmaceutical industry waste which pollutes waters. This waste contains complex compounds such as antibiotics and other chemicals that are difficult to decompose using conventional methods, and can disrupt water ecosystems. This article evaluates and discusses the effectiveness of bacteria in decomposing pharmaceutical industry waste and improving water quality.  The steps of bioremediation consisted of (1) isolation and selection of bacteria from polluted environments to obtain superior strains such as Pseudomonas sp., Bacillus sp., and Paraburkholderia xenovorans; (2) test the degradation ability of pharmaceutical compounds in the laboratory by adding bacteria to liquid media containing test compounds such as antibiotics and antiepileptics; (3) testing environmental conditions (pH, temperature, and oxygen availability) to find optimal conditions; and (4) application of bioremediation on a field scale by monitoring water quality based on chemical parameters (COD, BOD, and concentrations of pharmaceutical compounds) as well as biological parameters. Pseudomonas sp. degraded up to 80% of antibiotics within 7 days, while Bacillus sp. effectively reduces antiepileptic drug concentrations by up to 75% in 10 days. The combination of several bacterial species increases the effectiveness of degradation. Microbiological testing showed an increase in bacterial population diversity and density at treated sites, indicating restoration of the aquatic ecosystem.  It can be concluded that the strategic roele of bacteria in the bioremediation of pharmaceutical industrial waste in waters has proven to be effective and can be a sustainable solution for maintaining environmental quality. Implementation of this method requires optimal environmental conditions so that the degradation process takes place optimally and negative impacts on the ecosystem can be minimized.   Keywords: Bioremediation, Bacteria, Industrial Waste, Aquatic